Inter-distance differences in aiming error and visual perception influence shooting performance in basketball - Slegers, N. (Scientific Journal of Sport and Performance, 2022)
This study is the first to use inter-distance differences in shooting direction error to investigate the influence of visual perception on basketball shooting performance. Thirty-two experienced basketball athletes (NCAA Division I-III: n = 15, Canadian U Sports Association: n = 13, National Basketball Association: n = 4) attempted blocks of 25 jump shots from a near (free throw) and far distance (three-point attempt). Differences in the root-mean-square deviation of lateral direction error as distance increased, DeltaLDE, were used to measure an individual`s change in lateral accuracy as the target changed within their visual field. The mean DeltaLDE was -0.18 degrees (p < .001, 95% CI: -0.25 - -0.11) indicating that an individual`s lateral direction accuracy worsened as shooting distance decreased and external visual cues transitioned away from their central vision. Shooting performance had a strong positive correlation with DeltaLDE (r = 0.57, p = .001) indicating that better shooters have a higher ability to adapt to the changes in visual perception with distance and experienced smaller reductions in lateral accuracy as shooting distance decreased. These findings show that visual perception has a significant role in basketball shooting performance and that DeltaLDE is a valuable measure for assessing how an athlete`s proficiency in visual perception contributes to their performance.